Evaluasi Program Penanggulangan Stunting di Wilayah Kerja Puskesmas Panite Kecamatan Amanuban Selatan Kabupaten TTS Tahun 2023 - Oma Yuvita Lay Lado; Dominirsep O. Dodo; Masrida Sinaga (Yayasan Literasi Sains Indonesia, 2024)
Indonesia, as one of the developing countries, is still faced with nutritional issues such as stunting. Panite Health Center is one of the health centers in the TTS district with a high incidence of stunting in 2023, recording 817 cases or 32.30%. The aim of this research is to evaluate the implementation of the stunting mitigation program, which includes input, process, and output, in the working area of the Panite Health Center in Amanuban Selatan sub-district, TTS district, in 2023. This research employs a qualitative research type using a case study approach. The types of data used in this study include primary and secondary data. The research results indicate that input from human resources requires technical guidance and regular training for personnel involved, such as posyandu cadres, and that facilities and infrastructure need to be improved through regular maintenance. The implementation process of the stunting prevention program in the working area of the Panite Health Center has been quite good. The output in 2023 has been satisfactory, and the service coverage has reached the set targets. It is hoped that the Panite Community Health Center will pay more attention to knowledge about stunting for human resources.